Comparison of adnexal torsion in different phases of women’s life: a retrospective cohort study - J., Karthiga Prabhu; C., Shanmugapriya; Samal, Sunita; Ramraj, Balaji (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Ovarian torsion is one of the most common causes of emergency surgery in gynecology. Though it is more common in reproductive age group, it can occur in extremes of age group. So, we had analysed the clinical presentation, surgical characteristics, and causes of adnexal torsion among adolescent population, reproductive-age women, and postmenopausal women. Methods: Patients with adnexal torsion who were treated in department of obstetrics and gynecology, SRM Medical College Hospital and Research Centre from October 2016 to March 2019 were retrospectively analyzed. Results: Among the 53 cases of adnexal torsion during the study period, maximum (38, 71.6%) were in the reproductive age group. There were three patients with ovarian torsion during pregnancy. Acute pain abdomen was the significant presenting symptom in adolescent group compared to other two group (100% versus 80.6% versus 40%, p = 0.03). Adnexal pathology was in the ovary in 76% and isolated tubal pathology in 5%. Bilateral salpingo-oophorectomy with or without total abdominal hysterectomy was more commonly performed in postmenopausal patients (100%), as opposed to conservative surgery- detorsion and cystectomy in premenopausal women (56%). In Adolescent patients 62% had polycystic ovaries as intraoperative finding. Histopathology were benign except for a patient in postmenopausal age group who had granulosa cell tumour. Conclusions: An early identification of adnexal torsion is necessary in order to achieve conservative treatment in order to maximize the future reproductive potential in younger patients.